Low levels of Vitamin D an emerging risk for cardiovascular diseases: A review - Majeed, Farrukh (International Journal of Health Sciences, 2017)
Sunlight is regarded among greatest gifts that are presented in abundance to the human beings from the God. Sunlight is also a rich source of Vitamin D (Vit D) that prevents us from numerous ailments such as autoimmune disorders, various types of cancer, and the above all cardiovascular diseases (CVD). Evident from recent research that Vit D deficiency may be the cause for hypertension, cardiac autonomic imbalance, vascular endothelial dysfunction, metabolic syndrome, and even diabetes. Concurrently, many studies present research outcomes that are contradictory to earlier results and also raised a concern not for general public but also among their treating physicians. The sole focus of this review is to systematically present the available research data and critically evaluate the link between Vit D deficiency and development of risk factors for CVD.